2012
DOI: 10.1063/1.3691301
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigations of ThF and ThF+

Abstract: The electronic spectra of ThF and ThF(+) have been examined using laser induced fluorescence and resonant two-photon ionization techniques. The results from high-level ab initio calculations have been used to guide the assignment of these data. Spectra for ThF show that the molecule has an X (2)Δ(3/2) ground state. The upper spin-orbit component, X (2)Δ(5/2) was found at an energy of 2575(15) cm(-1). The low-lying states of ThF(+) were probed using dispersed fluorescence and pulsed field ionization-zero kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
107
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(124 citation statements)
references
References 45 publications
15
107
2
Order By: Relevance
“…Vibrational assignments are determined by comparing observed band intensities to Franck-Condon factors and a thermal vibrational distribution. With prior knowledge of vibrational constants from Barker et al [17], and our measured B values, Franck-Condon factors were calculated and compared to observed intensities for the initial bands measured. With the rotational and vibrational constants we have observed in ThF + , the vibrational (0, 0) is always the strongest band.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Vibrational assignments are determined by comparing observed band intensities to Franck-Condon factors and a thermal vibrational distribution. With prior knowledge of vibrational constants from Barker et al [17], and our measured B values, Franck-Condon factors were calculated and compared to observed intensities for the initial bands measured. With the rotational and vibrational constants we have observed in ThF + , the vibrational (0, 0) is always the strongest band.…”
Section: Results and Analysismentioning
confidence: 99%
“…The JILA experiment is currently using trapped HfF + [13], but ThF + is a promising candidate molecule for a future generation experiment due to its larger effective electric field [14,15,16] and longer-lived 3 ∆ 1 state. Assigning the ground state of ThF + has been experimentally challenging due to the proximity of both 1 Σ + and 3 ∆ states [17,18]. Calculations suggested that 3 ∆ 1 might be the ground state but uncertainties prevented a conclusive determination [19,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However for this species, the ab initio calculations are even more challenging, leading to larger theoretical uncertainties. The first spectroscopy of ThF + using PFI-ZEKE plus some LIF (unassigned) has recently been published [13], but, as was the case with HfF + , the higher excited states remain uncharacterized. By using highly non-linear fiber to broaden the comb spectrum [63] and a high repetition rate Ti:sapphire amplifier [64], we hope to cover over 2000 cm −1 with comb-vms.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…The energies of the lowlying 3 ∆ 1 , 3 ∆ 2 , and 3 ∆ 3 states were recently measured using pulsed-field ionization zero kinetic energy (PFI-ZEKE) spectroscopy [12,13]. Additionally, several isoelectronic species including TiO [14,15,16], TiF + and TiCl + [17,18] have been The eEDM experiment will utilize the J = 1 level of the 3 ∆ 1 metastable state.…”
Section: Introductionmentioning
confidence: 99%